The Applicability of Limiting Phase Angle Temperatures for Specifying Asphalt Binder Low Temperature Performance - Kristjan Lill; Karli Kontson; Andrus Aavik (The Baltic Journal of Road and Bridge Engineering)
The paper discusses the applicability of using limiting phase angle temperatures, measured in the Dynamic Shear Rheometer, for low temperature ranking of performance, in comparison with limiting low temperature grades in accordance with AASHTO TP 122-16 extended Bending Beam Rheometer method. During this study, also other low-temperature test methods were compared to each other. For this purpose, 13 asphalt binders were sourced from around North-Eastern Europe, twelve of which are currently used throughout Estonia as well as the neighbouring countries. The thirteenth was a high-quality Laguna Venezuela binder that is no longer commercially available in the region but was deemed suitable for comparison. Samples were tested to measure their needle penetration, Superpave Grades, Fraass breaking points, AASHTO TP 122-16 limiting low temperature grades and limiting 30° phase angle temperatures. Additionally, a correlation found in previous work was applied to the set of samples studied in this paper. Of the binders tested, the low temperature behaviour of the Venezuelan binder stands out with better performance. The analysis suggests that the twelve commercially available binders are from a similar source which was observed through their tendency to undergo thermo-reversible aging. The study shows that the phase angle approach provides a reasonable surrogate for the AASHTO TP 122-16 limiting low temperature grade. However, the latter should currently remain the preferred approach.